PERCEPTION AND SOCIAL RESISTANCE OR MSME ACTORS TOWARDS QRIS DIGITAL PAYMENT INNOVATION IN ENREKANG REGENCY - Nur Alfiah . JS; Firdaus W Suhaeb; Ahmadin (SOSIOEDUKASI, 2026)
This study aims to analyze: 1) MSME actors’ perceptions of the use of the QRIS digital payment system; 2) The factors that influence MSME actors to engage in social resistance to QRIS; 3) The impact of resistance in the MSME context. This research is qualitative with a phenomenological approach. The number of informants consists of eleven people, with the following criteria: 1) MSME actors who do not use QRIS, 2) MSME actors who already have QRIS but are using it reluctantly, 3) MSME actors who have acquired and printed a QR code but do not display it to customers, 4) MSME actors who use QRIS. Data collection techniques used are interviews and passive participant observation. Data validity was checked using source triangulation. The data analysis employed was data reduction, data presentation, and drawing conclusions. The results of this research show that: 1) MSME actors’ perceptions of the use of the QRIS digital payment system include a) perceived benefits, b) perceived ease, and c) perceived risks. 2) Factors influencing MSME actors to engage in social resistance include a) social influence, b) the habit of using cash, and c) digital payment technology literacy. 3) The impact of resistance in the MSME context is a reduction in business turnover/sales income. This study is significant because it provides an overview of MSME actors’ perceptions toward QRIS and the factors that cause them not to adopt or to resist QRIS, so it can serve as a basis for the government or related parties to develop strategies to eliminate social resistance among MSME actors and increase the use of QRIS in their business activities